Weryfikacja narodowościowa ludności rodzimej i rehabilitacja tzw. „volksdeutschów” w latach 1945-1949. - Kacprzak, Paweł (Wydawnictwo Poznańskie sp. z o.o., 2011)
The end of the Second World War and resulting from it new boundaries of Poland brought to light a very acute problem that required an immediate resolution of demographic and social matters. The predominant issue was the expulsion of the Germans from the Polish territory that needed to be conducted pursuant to the agreements of the Potsdam Treaty. The problem that arose in connection with that concerned the native (called autochthonous) German population in Poland. Consequently, a procedure to verify the nationality was developed, with the expectation that it would result in the acquisition of numbers of new citizens that Poland really needed. Another way of increasing the Polish population was through a rehabilitation procedure offered to those who had earlier enlisted as German nationals. While in the case of the former group (native Germans) the opposition among the Polish society was not very strong, the situation looked much different in the case of the latter, as there was a strong conviction in the society that those who had earlier renounced Polish citizenship deserved some kind of punishment. The paper deals with both issues and points to their complexity. The winding course of the Polish state’s policy towards those two groups of population in the first years after the end of the Second World War was dominated by the primary goal of Poland’s government to build a nationalistic state, had practically destroyed the plans to acquire their members as conscious Polish citizens.
VERIFICATION OF THE NATIONALITY OF THE AUTOCHTHONOUS POPULATION IN POLAND AND REHABILITATION OF SO CALLED “VOLKSDEUTSCHEN” BETWEEN 1945-1949.
Keywords: PRL; Polityka narodowościowa; Volksdeutsch